Census of population Pakistan, 1961 : Vol. 3 - Pakistan Office of the Census Commission (Karachi : Manager of Publications, 1961)
Collection of publications relating to Pakistan's 1961 census of population and housing, consisting of : <7> Bulletins; <10> Reports and <27> District census reports
Contents: v. 3 : West Pakistan : Tables & report.
Keywords: Pakistan -- Census